‘You teach it, and then I go off and try to soak it all up’: A qualitative investigation of first year student expectations during transition - Tomlinson, Amy; Killingback, Clare (Journal of University Teaching and Learning Practice, 2025)
Student expectations are an important factor affecting successful transition to higher education. Expectations of the wider university experience have been well researched, however learning and teaching specific expectations require further exploration in order to facilitate achievement, satisfaction and retention. The aim of this qualitative study was to understand first year student expectations of learning and teaching when transitioning to university. Semi-structured interviews were conducted with twelve first-year Sport Rehabilitation students. Data were analysed using thematic analysis and four key themes identified: student responsibility, the classroom, learning beyond the classroom, and transition. Students expect learning within the classroom to be largely passive, but expect to take responsibility for their learning outside of the classroom and adopt an active approach to developing understanding. Family, peers, previous educators, social media, and room layout contributed towards informing expectations. These insights will enable programme teams to provide informed support for students in reframing their expectations to align with the realities of university study and contemporary learning theory. Future research should explore expectations of learning and teaching across other disciplines, and investigate the effectiveness of interventions that work to align student expectations with the realities of study on university programmes.